PENGARUH MODEL PEMBELAJARAN INQUIRI TERHADAP PRESTASI BELAJAR FISIKA SISWA SMP NEGERI 8 MATARAM - Prayogi, Saiful; Gummah, Syifa’ul; Ahzan, Sukainil; Heryani, Nunik (Lensa: Jurnal Kependidikan Fisika, 2014)
This study aims to determine the effect of inquiry learning model on student physics achievement in junior high school. The method used is experimental research. The sample used are; grade VII-D students as many as 27 people as control class, and level VII-G as many as 27 people as experimental class. The sample selection was done by purposive sampling technique. The data were collected by pre-test and post-test in both classes. The average pre-test in the experimental class is 28.04 and 30.11 for the control class. The average post-test score in the experimental class is 74.41 and 69.26 for the control class. The analysis result using t-test obtained t-test of 1.82 and t-table is 1.67. The value of t-test is greater than t-table at 5% and dk is 52. We conclude that there has been a significant influence of inquiry learning model on physics learning achievement.